Strategi Pengembangan Usaha Penangkar Bibit Jeruk Siam (Citrus Nobilis) Di Kabupaten Sambas - Radian, Manawar Jeffry, Abdul Hamid A. Yusra, (Jurnal Social Economic of Agriculture, 2017)
This research was conducted in Orange Siamese Enterprises seed breeder, seed breeding centers of Tangerine, which is in Sambas, West Kalimantan. The research was conducted from August to October 2015. The study was conducted by descriptive method with case study approach. The sampling method used is stratified sampling, the population is 16 seed breeder Tangerine, in Sambas, West Kalimantan. Data collection methods consist of primary data and secondary data. The research method using SWOT analysis or Strengts, Weaknesses, Opportunities and Threats.Development Seed breeder Tangerine in Sambas, West Kalimantan, aternatif most appropriate, namely by using SO strategy, because this strategy has the highest value, which is at 19.3. Where the strategy SO is a strategy of using force to take advantage of opportunities for farmers to seed breeder citrus able to develop its growth strategy, the development of seedlings tangerine.Keywords : Strategy Development, Business breeders, seed citrus